Promoting healthy eating in primary health care from the perspective of health professionals: a qualitative comparative study in the context of South America (2018)
ABSTRACT: Educational interventions designed to promote healthy eating are essential in primary health care. Nevertheless, given the nutrition controversies about what is healthy, the contradictions created by the media, and the situation of users with complex needs, the prioritization of the themes to be addressed in the services has scarcely been described in the planning process. This study aimed to identify the process of implementing the themes discussed by health professionals in nutrition education groups in two primary health care models. Methods: Our study followed a qualitative comparative approach. It included the systematic observation of nutrition education group meetings to identify the key messages addressed and semi-structured interviews with health professionals in São Paulo, Brazil, and in Bogotá, Colombia. We used thematic networks to classify the messages and the collective subject discourse technique to organize the information obtained from interviews. We observed 28 nutrition education groups in São Paulo, and 13 in Bogotá, and conducted 27 interviews with nutritionists in each city. Results: The messages identified were grouped into four global themes: feeding habits, life cycle, disease, and “being a multiplier”. The process of implementing the themes, understood as identification, selection, consultation, and application of themes, is intermediated by social representations of the health professionals about service requirements, training and professional performance, and the relationship with users. Two notions shape these representations: Control, although the time and the physical space dedicated to health services are restricted to the disease in São Paulo, in Bogotá only limited health promotion is provided; and specificity, which is portrayed as therapeutic support within a more educational model in São Paulo and as health promotion training courses within a prescriptive model in Bogotá. Conclusions: Understanding the process of implementing the themes discussed in nutrition education groups can reveal mechanisms that support the approach to themes on healthy eating, including communicative and educational adaptations of health professionals. This study contributes to the discussion about educational models in health care and their effects on the qualifications of health professionals within the service, especially those included in the context of low- and middle-income settings. Keywords: Nutrition, Health systems and services in low and middle-income settings, Primary care, Health promotion/prevention/screening, Qualitative research